Inactivation mechanism and kinetics of dielectric barrier discharge plasma against Escherichia coli O157:H7 in phosphate-buffered saline - Niu, Liyuan; Zhang, Dianhe; Wang, Bohua; Xiang, Qisen; Bai, Yanhong (CYTA: journal of food, 2024)
This study investigated the inactivation mechanism and kinetics of dielectric barrier discharges (DBD) plasma against Escherichia coli O157:H7. DBD plasma exhibited a remarkable bactericidal effect, and the inactivation kinetics was well described with the Weibull model. Using the ambient air as the working gas, surviving E. coli O157:H7 in phosphate-buffered saline achieved an undetectable level (<10 CFU/mL) after treatment at 18 W for 60 s. DBD plasma altered cell morphology, destructed both the outer and inner membranes, and increased intracellular reactive oxygen species levels. Moreover, DBD plasma significantly decreased the pH of the suspended medium, and increased its oxidation reduction potential and active species levels, which could be mainly responsible for microbial inactivation. The presence of glutathione or N-acetyl-L-cysteine weakened the antibacterial activity of DBD plasma due to their reactive oxygen and nitrogen species (RONS) scavenging capacity, demonstrating that RONS generated by DBD plasma played important roles in decontamination.